The effect of thyroxin on the renal function of asphyxiated neonates - Rostenberghe, Hans Van; Halder, Dinesh; Razak, Abdul Razif Abdul; Abdullah, Yunus
Thyroxin has been shown to have a beneficial effect on renal function in cases of pending renal failure in animal studies. Studies of the use of thyroxin in humans in pending renal failure are scarce. The aim of this study was to assess the effect of oral thyroxin on the renal function of asphyxiated neonates who often have renal impairment.A randomised controlled trial was conducted. Two groups of 15 term asphyxiated neonates were studied. Thyroxin (50) was given on day 1, 2 and 3 of life for the treatment group and placebo was given for the control group. Renal function was studied on day 1 and day 4 of life. The two groups were not statistically significant different for gestational age, birthweight, severity of asphyxia, pregnancy or delivery complications, fluids administered and drugs used. There was no significant difference in urine output, creatinin clearance and fractional excretion of sodium on day 1 but there was a trend towards a worse renal function on day 1 in the treatment group. The creatinin clearance was significantly better in the treatment group on day 4 (p = 0.017).Urine output and fractional excretion of sodium on day 4 were better in the treatment group but the differences did not reach statistical significance (p of 0.14 and 0.057 respectively). Statistical analysis on the differences between day 4 and day 1 showed statistical significance only for Clcreat : Clcreat day 4 - Clcreat day 4 was 52.6 (+/-32.4)for the thyroxin group and 7.3 (+/-7.8) for the controls (p= 0.006). These data support that thyroxin may have a significant beneficial effect on the renal function in patients with perinatal asphyxia. Thyroxin may be proven useful in future for patients with pending renal failure.